O‘QUVCHILARDA GENETIKA BO‘YICHA BILIMLARNI KUZATISHNING PEDAGOGIK ASOSLARI. (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2026)
This chapter deeply analyzes the pedagogical foundations for effectively monitoring students' knowledge in genetics, set against the complexity and societal importance of genetic education. It addresses global issues associated with low genetic literacy rates, exploring innovative pedagogical approaches and assessment tools aimed at identifying and resolving misconceptions. The chapter discusses theoretical frameworks of genetic education, diagnostic assessment methods, common misconceptions, and strategies for overcoming them, based on a scientific literature review. Finally, recommendations for Uzbekistan's education system are provided, alongside future research directions.